Climate shocks, adaptive mechanisms and household energy transition in Uganda - Elasu, Joseph; Ntayi, Joseph Mpeera; Adaramola, Muyiwa S.; Buyinza, Faisal; Atukunda, Ronnette; Ngoma, Muhamad (Springer International Publishing, 2024)
Abstract Nearly 41% of the global populace depends on unclean fuels for cooking. As a result, about 4 million premature deaths connected to household air pollution are registered annually. Worryingly, over 2.1 billion people are estimated to continue using unclean fuels by 2030 if no strong policy actions are taken to alter the status quo. Climate parameters including; temperature, solar radiation, wind, and moisture have been widely touted as having an impact on multidimensional energy poverty, their effect on household energy consumption and subsequent transition to cleaner fuels is seldom investigated in Uganda. The purpose of this study is to investigate the effect of climate shocks, and adaptation mechanisms on household energy transition in Uganda. The study adopted a panel data methodology employing an ordered logit model with random effects to estimate the effect of climate shocks and adaptation mechanisms on household fuel transition from high to low-pollutant cooking fuels in Uganda. The findings revealed that climate shocks, adaptation mechanisms significantly affect household energy transition in Uganda. The study recommended that policies aimed at enhancing detection and report of early warning signs should be emphasized. Furthermore, investing in an insurance scheme especially for people living in climate shock prone areas can help households to cope up with shocks are eventually transition to clean cooking fuels.